Re-reading the book Heart (Praxis Educativa, 2012)
The reissue of Heart by Edmund De Amicis (first puljlished 1886) brings me - together with the school memories of its reading - opposing feelings of astonishment and multiple queries to elucidate. The present irruption of Heart into Italiah television, through a disrespectful adaptation, opens the debate on its new introduction into Italian schools. I then recall the original narrative - a true impact on emotions - accompanied by our teachers' questions, that made us penetrate the magic world generated by prose and poetry when merged into the double play of questions and answers. And thus appears the text, moral and discursive, loaded with affectivity, bringing to us the myth of the hero from the Italy of "national unity". I hypothesise that De Amicis wrote it for purely ideological reasons. Through Heart, the imprints of the prevailing ethics and family and military morals are reproduced in school, and return home enlarged and polished. The principle of authority, the submissive relationship with power appear in these stories that directly impact on the "heart". The same fascism and other totalitarianisms would later do with other discourses. However, the Argentinean teachers that used it, did it from a purely didactic and formative outlook, in favour of motherly love, sincerity, loyalty.
Keywords: XIX century narrative; reissue; media; ideology